Los nuevos alquimistas : una sociología de la restauración desde México - Vega Cárdenas, Alfredo (ITESO, Universidad Jesuita de Guadalajara, 2018)
Vega Cárdenas delivers a new and reflexive perspective on restoration that enables the agents involved in this field to incorporate both specific materials and techniques in the restoration activity theoretical, political, social, economic and philosophical factors, to preserve, preserve and socialize the cultural legacy.